Behavioral and biochemical issues in substance abuse - George, Frank Richard; Clouet, Doris H.; Stimmel, Barry, 1939- (Haworth Press, 1991)
This excellent book is a concise yet thorough examination of the important and emerging field of the study of biological risk factors in drug abuse. Historically, drug abuse research has concentrated on the contributions of environmental and behavioral factors as the major influences on addiction. The revelatory studies in this volume examine the genetic contributions to drug taking behavior through the use of animal models, cellular experiments and human clinical studies. Behavioral and Biochemical Issues in Substance Abuse provides for the first time in one volume, up-to-date, easily digeste.